Relasi Islam dan Negara Perspektif Kiai Haji Ahmad Siddiq Jember - Muhammad Izul Ridho; Robiatus Solehah (Mozaic: Islamic Studies Journal, 2022)
At least in the last decade, the Indonesian people have again been plagued by the question of what the ideal relationship between Religion and State is. On the one hand, there are small groups of Muslims who want Islam as a religion to be fully incorporated into the state as the ideology and principle of the state, with the aim of making Indonesia a complete Islamic state. On the other hand, groups that have extremely rejected the involvement of religion in state regulation have also begun to show their rationale, by reducing Pancasila to trisila and ekasila, which can clearly reduce the universal values ​​of Pancasila as basis of Indonesia state. In this article, the author describes the thoughts of Kiai Haji Ahmad Siddiq in order to provide solutions and streamline the understanding of relationship between Religion and the State. Kiai Siddiq revealed that Pancasila is a unified whole that cannot be reduced and applied to just one, and the first precept, "Belief in One Supreme God" is the basis that must influence the other precepts.